Reproductive condition and tentacle extirpation in malayan achatina fulica (Pulmonata) - Berry, A.J.; Chan, L.C. (CSIRO Publishing, 1968)
Some individuals of A. fulica in Malaya have active gonads at all times of the year. Several criteria indicate, however, that reproductive activity is greatest in July-December and declines to a minimum in March. There is some evidence that this cycle is related to rainfall, and that year-by-year differences in rainfall affect fluctuations in reproductive condition. A. fulica with their ocular tentacles removed produced significantly more shelled eggs than normal snails and also had more large oocytes in their gonads. When albumen glands were full, numbers of shelled eggs were significantly greater than when albumen glands were reduced. In snails with small albumen glands, removal of tentacles caused oocytes in the gonad to increase more markedly than shelled eggs. It is suggested that the general nutritional condition of the snail affects its ability to form complete shelled eggs, but not its ability to produce oocytes in the gonad. The latter appears to be under a hormonal control involving the tentacles, rather like that proposed by Pelluet and Lane (1961). © 1968, CSIRO. All rights reserved.